2022
DOI: 10.3390/pharmaceutics14122840
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Temperature Evolution during Nanomilling of Drug Suspensions via a Semi-Theoretical Lumped-Parameter Model

Abstract: Although temperature can significantly affect the stability and degradation of drug nanosuspensions, temperature evolution during the production of drug nanoparticles via wet stirred media milling, also known as nanomilling, has not been studied extensively. This study aims to establish both descriptive and predictive capabilities of a semi-theoretical lumped parameter model (LPM) for temperature evolution. In the experiments, the mill was operated at various stirrer speeds, bead loadings, and bead sizes, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…We have seen in this dataset that an increase in tip speed (or rotation speed for a given mill) and bead loading both led to higher T avg. This finding is in line with earlier heat transfer–generation studies [ 65 , 66 , 67 ], which demonstrated that a higher power consumption was observed at the higher rotation speed, and that higher bead loading was the origin of higher heat generation and ensuing temperature rise.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We have seen in this dataset that an increase in tip speed (or rotation speed for a given mill) and bead loading both led to higher T avg. This finding is in line with earlier heat transfer–generation studies [ 65 , 66 , 67 ], which demonstrated that a higher power consumption was observed at the higher rotation speed, and that higher bead loading was the origin of higher heat generation and ensuing temperature rise.…”
Section: Resultssupporting
confidence: 91%
“…Bead size can be an important process parameter as it may provide combined advantages of faster breakage [ 21 , 50 , 64 ], lower heat generation rate [ 65 , 66 , 67 ], and lower media wear [ 21 , 64 ]. However, its impact on the breakage rate may be more subtle because it has counteracting microhydrodynamic trends where smaller beads capture drug particles more frequently but apply less stress upon contact [ 20 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, one of the most challenging issues encountered in both the pharmaceutical industry and pharmaceutical studies has been drug candidates with low water solubility [ 1 ]. The main challenges are that the dose-response linearity of drugs with low water solubility may decrease, and unexpected collapse of the drug may be encountered after administration, leading to decreased patient compliance and decreased bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the processes in wet stirred and ball mills is challenging. It requires simultaneous modeling of the complex physics of interactions between the grinding media, the moving mixing elements, and the grinding materials [20,21]. According to Esteves et al [22], in fine grinding applications, the energy efficiency of gravity-induced stirred mills is higher than that of traditional ball mills.…”
Section: Introductionmentioning
confidence: 99%